Behind the Science literacy of Filipino students at PISA 2018: A Case study in the Philippines’ Educational System - Jefferson M Cordon; John Domnique Benedict Polong (Cahaya Ilmu Cendekia Publisher, 2020)
Purpose of the study: To find out the struggle to build students' Science literacy experienced by the Philippines in the PISA 2018 results. Methodology: the methodology used uses Case Study design. The method used by collecting facts from various data, learning curricula, culture and some Science discourse related to science literacy and PISA score. Various facts are analyzed by grouping and classifying and drawing conclusions from the discussion. decision-makers Findings: integration efforts from teachers, schools, and curriculum continue to be improved by the government to improve the quality of education, although the results of the Science literacy of students in PISA 2018 have not been sufficient. Applications of this study: This study will provide an open picture to provide innovation, a literature study for the basis of thinking the importance of overall integrase in increasing Science literacy of students, not just teachers Novelty/Originality of this study: Cultural influences on students' science literacy.